UMPSA researcher Associate Professor Ir. Dr. Chin Siew Choo produces Brewcrete, eco-friendly sustainable cement from coffee waste - Nur Hartini, Mohd Hatta (UMPSA, 2025)
PEKAN, 18 August 2025 – Looking at coffee waste, the by-product of the brewing process increasingly produced by Malaysians who drink an average of 2.38 cups of coffee a day (totalling around 3 billion cups daily) and generating about 100 tonnes of coffee waste per day, a team of researchers from Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) led by lecturer from the Faculty of Civil Engineering Technology (FTKA), Associate Professor Ir. Dr. Chin Siew Choo, has produced Brewcrete.